Nicomachean ethics - Aristotle (Dover Publications, 1998)
This enduringly profound treatise was first used by the students of Aristotle's famous Athenian school, the Lyceum; since then it has exercised a lasting effect on Western philosophy and continues to resonate for modern readers. Aristotle identifies the goal of life as happiness and discusses its attainment through the contemplation of philosophic truth. Inexpensive edition of a literary and philosophical classic.